2022
DOI: 10.3389/fpsyt.2021.730921
|View full text |Cite
|
Sign up to set email alerts
|

Theories of Change and Mediators of Psychotherapy Effectiveness in Adolescents With Externalising Behaviours: A Systematic Review

Abstract: BackgroundExternalising behaviours are becoming a remarkably prevalent problem during adolescence, often precipitating both externalising and internalising disorders in later adulthood. Psychological treatments aim to increase the social functioning of adolescents in order for them to live a more balanced life and prevent these negative trajectories. However, little is known of the intervening variables and mediators involved in these treatments' change mechanisms. We conducted a systematic review, exploring t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…Recognising the significance of outcome measures, the development of a shared core outcome set (Mestre Navas et al, 2022) is recommended, defining the minimum best-practice measurement requirements. In the absence of such a set, researchers can turn to resources like the COSMIN (COnsensus-based Standards for the selection of health Measurement Instruments) website or engage in collaborative design through methods like Delphi studies (as has been done in Australia (Hill et al, 2019)) or consensus statements (co-produced by stakeholders).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognising the significance of outcome measures, the development of a shared core outcome set (Mestre Navas et al, 2022) is recommended, defining the minimum best-practice measurement requirements. In the absence of such a set, researchers can turn to resources like the COSMIN (COnsensus-based Standards for the selection of health Measurement Instruments) website or engage in collaborative design through methods like Delphi studies (as has been done in Australia (Hill et al, 2019)) or consensus statements (co-produced by stakeholders).…”
Section: Discussionmentioning
confidence: 99%
“…While most studies mentioned theory of change, it was not always clear whether, or how, the theory of change related to outcome measures. While this is difficult to quantify (Aggarwal et al, 2021; Mestre Navas et al, 2022), as goals and mechanisms of action become clear, outcome measures can be chosen so as to reflect change mechanisms. Ideally, valid and reliable measures should be prioritised over untested outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…It thus seems that delivering emotion regulation skills training in a joint format has the potential to impact the parent-child relationship. Earlier research has shown that improved family relationships and communication are mechanisms of change in the treatment of adolescent externalising behaviour [ 56 ], and it would be interesting to further investigate the relationship between family functioning and emotion regulation skills.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a systematic review reported that adequate behavioural control of adolescents' peer behaviour and a more positive balance in their relationships with their parents seemed to buffer the effects of mental health problems, increasing their effectiveness. Unfortunately, other mediators, such as emotional, cognitive, and, more importantly, environmental, such as low neighbourhood socioeconomic status, delinquency, exposure to adverse events in the population at risk, or high rates of substance use, are strikingly neglected in the literature (Mestre et al, 2022).…”
Section: E Ectiveness Of Interventionsmentioning
confidence: 99%